Skeletal Regeneration by Mesenchymal Stem Cells: What Else? - Andrades, José A.; Claros, Silvia; Jiménez-Palomo, Pedro; López‐Puertas, José Ma; Zamora‐Navas, Plácido; Guerado, Enrique; Monleón, Manuel; Araque, María C.; Becerra, José (IntechOpen, 2011)
None